2021
DOI: 10.1152/physiolgenomics.00022.2021
|View full text |Cite
|
Sign up to set email alerts
|

Chronic jetlag-induced alterations in pancreatic diurnal gene expression

Abstract: Cell-autonomous circadian clocks exist in nearly every organ and function to maintain homeostasis through a complex series of transcriptional-translational feedback loops. The response of these peripheral clocks to external perturbations, such as chronic jetlag and shiftwork, has been extensively investigated. However, an evaluation of the effects of chronic jetlag on the mouse pancreatic transcriptome is still lacking. Herein we report an evaluation of the diurnal variations encountered in the pancreatic tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(53 citation statements)
references
References 45 publications
3
45
0
Order By: Relevance
“…In prior transcriptomic experiments investigating the effects of CJ on the pancreas, we observed that the core clock genes remained robustly rhythmic despite perturbations in the LD cycle. However, we found that there was a consistent, approximately 4-hour, phase shift of nearly all the core clock genes 14 . This translated to shifts in the phase of genes for many pathways important for lipid metabolism.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…In prior transcriptomic experiments investigating the effects of CJ on the pancreas, we observed that the core clock genes remained robustly rhythmic despite perturbations in the LD cycle. However, we found that there was a consistent, approximately 4-hour, phase shift of nearly all the core clock genes 14 . This translated to shifts in the phase of genes for many pathways important for lipid metabolism.…”
Section: Resultsmentioning
confidence: 67%
“…13 Our laboratory recently carried out a whole-pancreas transcriptomic evaluation of WT mice subjected to 1 month of a chronic jetlag (CJ) protocol that mimics human shiftwork. 14 During our evaluation, we found that transcriptomic signatures corresponding to multiple lipid metabolism-related pathways were preferentially phase shifted (ie, shift in the timing of peak 24-hour expression). These novel data prompted us to understand the downstream effects on the pancreatic cellular lipid content, yet no study that evaluates the pancreatic lipidome exists.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…5,6,26,27 To further evaluate the role of clock dysfunction in PDAC development, we subjected mice to a wellcharacterized chronic jetlag (CJ) protocol. 9,25 Interestingly, in KC mice prone to PDAC formation, we found that CJ promoted an increase in FI/PanIN development leading to more advanced lesions. 10 We then used a series of scRNAseq experiments to identify fibroblasts as the susceptible cell type to CJ within the developing PDAC tumor microenvironment.…”
Section: Discussionmentioning
confidence: 70%
“…Starting at 4-6 weeks of age, KC mice were subjected to either a normal circadian (NC) 12-hour light: dark (LD) cycle condition, or a chronic jetlag protocol (CJ) known to mimic altered sleep-wake cycles. 6,9 CJ consisted of a 12-hour LD cycle, phase-shifted forward 4 hours every 2-3 days. Mice were kept under their respective conditions until the study endpoint at 5 and 9 months of age.…”
Section: Materials and Methodologymentioning
confidence: 99%